A Review On Natural And Artificial Methods Of Fruit Ripening, Benefits & Hazards. - Dwivedi, Ashutosh; Singh, Archana; Agrawal, Sarvesh Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Fruits are the part of healthy and balanced diet which play an important role in nutrition, metabolic activities and heath of individuals by supplying necessary and essential growth regulating factors. Fruits are also advised by physician as indicated or contraindicated in different health condition or disorders. It is widely described as a part of Ahara varga under Phala varga in all Ayurvedic literatures where quality and indications of ripened and un ripened fruits and vegetables are described. There are various natural and artificial methods available for ripening, out of which some are safe. Commercial artificial ripening of fruits by ethylene are considered safe to eat. It allows the picking of many fruits raw and shipping them globally whereas artificial ripening by Calcium carbide is legally banned worldwide may cause many of health hazards. In this paper, a review study on fruits and their ripening methods is presented to develop understanding about different procedures, ripening agents, and their effects on health.